Morphological Change and Semantic Shift in Globalized Languages: A Cross-Linguistic Study - Ishak Bagea; Sitti Agustina; Miki Yuliandri; Amina Azhigali (Journal of Humanities Research Sustainability, 2026)
Background. The globalization of languages has led to significant morphological changes and semantic shifts across linguistic systems. As languages come into contact with each other through trade, migration, and technological advancement, their structures evolve to accommodate new social and cultural realities. Understanding how these changes manifest and what they reveal about language use in a globalized world is crucial for both linguistics and cultural studies. Purpose. This study aims to investigate the morphological changes and semantic shifts occurring in languages under the influence of globalization. Specifically, it examines how lexical items from dominant global languages (e.g., English) are integrated into other linguistic systems, and how their meanings and forms transform in the process. Method. A cross-linguistic comparative approach is employed, focusing on a selection of languages that have been significantly influenced by global languages. Data were collected from corpora, texts, and spoken language samples across multiple languages. The study applies both qualitative and quantitative methods, including morphological analysis and semantic mapping. Results. The study finds that globalization has led to both the simplification of morphological structures and the expansion of semantic fields, particularly in languages with extensive borrowing from global lingua franca languages. In many cases, the meaning of loanwords shifts to fit local contexts and cultural nuances. Conclusion. This research highlights the dynamic nature of language change in response to globalization, providing insights into how languages adapt and transform in a globally interconnected world.